Factor Analysis Of Rejection Of Covid-19 Vaccination In Rural And Urban People Communities In Langkat Regency In 2022 - Claudia, Khalisa; Khairunnisa, Khairunnisa; Wiryanto, Wiryanto (Publisher Cv. Inara, 2023)
Coronavirus is one of the diseases with the fastest transmission rate that is currently disturbing the world. One alternative that could be done to anticipate this complaint was to administer a vaccine as an antidote to this virus. The purpose of this study was to determine the factors contributing the rejection of Covid -19 vaccination in rural and Urban communities in Langkat Regency in 2022. The research method used in this research combined quantitative methods and qualitative methods. With a total sample of 260 people divided into 2 groups (rural and Urban comunity, the number of samples in Urbancomunity areas was 130, and the number of samples in rural community areas was 130. The results of this study indicated that the community's rejection of vaccines was caused by several factors, namely anxiety about side effects (an average of 15.37 ± 2.494 for rural communities) and fear of being injected. 13.42 ± 2.539 for rural communities that had never been vaccinated and 13.75 ± 3.419 for Urban people, rejection of community leaders as much as 13.42 ± 3.452 for village people; doubts about vaccine halalness as much as 14.88 ± 2.698 for Urban people; fake news for about 14.68 ± 2.904 for Urban people, did not believe in the virus 12.93 ± 3.216 for people in cities, and the uncertainty of the vaccine program as much as 12.71 ± 2.997 for Urbanpeople. From the results of the analysis, it could be seen that the largest level of rejection was carried out by Urban people communities.